Hardship in the headlines: global poverty and neocolonialism in western news media - Fox,Laura (2016)
Poverty is one of the most significant issues facing the world today. Although Western news media often report on the manifestations of poverty-famine, overcrowding, epidemics, or natural disasters-they rarely reflect the political, economic, and ideological structures that have directly caused and continue to exacerbate it on a global scale. This article argues that Western news media communicate global poverty, as a pressing issue, but ultimately fail to point out underlying causes or suggest any changes to the status quo. This fosters an understanding of poverty as a series of events, rather than the lived daily experience of many. This article, therefore, investigates the structures of neocolonial capitalism and neoliberal ideologies that gained momentum in the 20th century and continue to frame the content of news media today. Discussing the concepts of ‘compassion fatigue' and Anthony Downs' ‘issue-attention cycle', this article is a normative analysis of news media, exploring new ways to educate citizens on the global political economy. Drawing on the work of Lauren Berlant and Robert McChesney, this article ultimately discusses new ways of communicating poverty, which will require an acknowledgement of neocolonialism and a rethinking of crisis as lived daily experience.